PENGARUH DESAIN MASKER KAIN DAN SELERA KONSUMEN DITENGAH PENYEBARAN WABAH VIRUS COVID-19 TERHADAP TINGKAT PENDAPATAN KONVEKSI VOLUNTEER KABUPATEN OGAN KOMERING ULU - Rini Apriyani; Hema Malini; Yoga Taufik Ramadha (KOLEGIAL, 2022)
The purpose of this study was to determine the effect of cloth mask designs and consumer tastes amid the spread of the covid-19 virus outbreak on the income level of Convection Volunteers in Ogan Komering Ulu Regency. The method used is descriptive method. The sample in this study were consumers who ordered cloth masks again using 30 people with a saturated sampling technique. Results Based on the research and discussion that has been done, there is an influence of cloth mask design and consumer tastes on the income level of Convection Volunteers in Ogan Komering Ulu Regency. Based on the multiple linear regression equation is Y=2.227 + 0.672X1 + 0.212X2, and the correlation value of 0.800 is in the 0.800-1000 position, so it is declared very strong while the R square number (coefficient of determination) is 0.640, this indicates that the contribution of the fabric mask design variable (X1), consumer tastes (X2), and income level (Y) Volunteer convection in Ogan Komering Ulu Regency is 64%. Based on the data obtained, the tcount of the cloth mask design variable was obtained with a tcount of 3,965 where the tcount value was more than the ttable value (3.965>2.051). Then there is an influence between the fabric mask design variable (X1) on the income level (Y) of Convection Volunteers in Ogan Komering Ulu Regency. Then for the consumer tastes variable, the tcount value is 1.159 where the tcount value is smaller than the ttable value (1,159 < 2.051). So there is no influence between the variables of consumer tastes (X2) on the income level (Y) of Convection Volunteers in Ogan Komering Ulu Regency.